2008
DOI: 10.1007/s11104-008-9728-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between N2O, NO, and N2 fluxes from fertilized and irrigated dryland soils of the Aral Sea Basin, Uzbekistan

Abstract: Microbial respiratory reduction of nitrous oxide (N 2 O) to dinitrogen (N 2 ) via denitrification plays a key role within the global N-cycle since it is the most important process for converting reactive nitrogen back into inert molecular N 2 . However, due to methodological constraints, we still lack a comprehensive, quantitative understanding of denitrification rates and controlling factors across various ecosystems. We investigated N 2 , N 2 O and NO emissions from irrigated cotton fields within the Aral Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 43 publications
6
31
3
3
Order By: Relevance
“…The latter value is at the upper level of N 2 O emissions from the limited amount of data available for irrigated cotton reported from other countries (Mahmood et al 2008;Scheer et al 2008;Liu et al 2010;Watts et al 2015) and of a similar magnitude to that reported by Grace et al (2004) at the same site. Scheer et al (2008) reported a comparable response to N in irrigated cotton in Uzbekistan (6.5 kg N 2 O-N ha -1 ) after application of 250 kg N ha -1 . The Australian cotton studies were all undertaken on alkaline heavy black clays that rapidly become anaerobic, producing ideal conditions for prolonged periods of denitrification (Rochester 2003) compared with the relatively free-draining sandy loams and loams studied in other countries.…”
Section: Resultssupporting
confidence: 87%
“…The latter value is at the upper level of N 2 O emissions from the limited amount of data available for irrigated cotton reported from other countries (Mahmood et al 2008;Scheer et al 2008;Liu et al 2010;Watts et al 2015) and of a similar magnitude to that reported by Grace et al (2004) at the same site. Scheer et al (2008) reported a comparable response to N in irrigated cotton in Uzbekistan (6.5 kg N 2 O-N ha -1 ) after application of 250 kg N ha -1 . The Australian cotton studies were all undertaken on alkaline heavy black clays that rapidly become anaerobic, producing ideal conditions for prolonged periods of denitrification (Rochester 2003) compared with the relatively free-draining sandy loams and loams studied in other countries.…”
Section: Resultssupporting
confidence: 87%
“…Accordingly, the reported fertilizer-induced NO emission ratios varied from 0.003% to 11% (Yan et al, 2003). Although many studies have investigated the exchange of NO X between various agricultural fields and the atmosphere Stohl et al, 1996;Veldkamp and Keller, 1997;Zheng et al, 2003a,b;Mu, 2006, 2007;Scheer et al, 2009;Yu et al, 2008), the available data are still limited to accurately estimate NO emissions from agricultural fields. In the empirical model of Yienger and Levy (1995), 2.5% of the fertilizer N applied to soil was assumed to be emitted as NO (based on the arithmetic mean of eight reports).…”
Section: Introductionmentioning
confidence: 99%
“…Davidson et al (1991) provided a WFPS threshold for determination of source process, with a value of 60 % WFPS as the borderline between nitrification and denitrification as source processes for N 2 O production. The WFPS in all treatments in our study was larger than 70 %, above this 60 % threshold, and referred to as the "optimum water content" for N 2 O by Scheer et al (2009), so we can be confident that denitrification was likely to have been the main Table 7 source process in our experiment. In addition, Bateman et al (2004) observed the largest N 2 O fluxes at 70 % WFPS on a silty loam soil, lower than the 80 % value for the largest fluxes from the clay soil in our study (Fig.…”
Section: Isotopocules Of N 2 Omentioning
confidence: 58%